1986
DOI: 10.1111/j.1365-2672.1986.tb04296.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical taxonomy of Bacillus isolated from orally administered drugs

Abstract: Numerical taxonomy procedures were used to study 118 strains of Bacillus isolated from non-sterile drugs prepared for oral administration. Similarities between pairs of strains were calculated by the simple matching coefficient of Sokal and Michener (SSM). Each strain was tested for 60 unit characters and three clusters were defined. The strains in each cluster presented a similarity level of at least 60%. Cluster A comprised the strains identified as Bacillus cereus (SSM = 93.13%), cluster B contained three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…The results of this study showed that Bacillus species were the bacteria most frequently found in orally and topically administrated medicaments, and this observation agrees with the work of other investigators [1,2].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study showed that Bacillus species were the bacteria most frequently found in orally and topically administrated medicaments, and this observation agrees with the work of other investigators [1,2].…”
Section: Discussionsupporting
confidence: 93%
“…Several papers have been published reporting the contamination of non-sterile pharmaceuticals with microorganisms [1][2][3]. The presence of microorganisms in pharmaceuticals is undesirable because they may cause spoilage of the product and may present an infection hazard to the consumers or patients.…”
Section: Introductionmentioning
confidence: 99%
“…et al 1980). It has also been reported previously that the genus Bacillus is the most frequent contaminant in oral drugs, with B. cereus as a common contaminant (Willemse-Collinet et al 1978;Gil et al 1986). We have observed, as in previous studies, that stability is maintained in the morphological characteristics of the bacterial cells and colonies (Gibson & Gordon 1974;Claus & Berkeley 1986).…”
Section: Discussionsupporting
confidence: 89%
“…The contaminants most frequently found are those that can resist environmental agents and which have little nutritional need; prominent among these are the spore-forming rods of the genus Bacillus (Willemse-Collinet et al 1978;Devleeschouwer et al 1980;Economou-Stamatelopoulou & Papavassiliou 1983;Garcia Arribas et al 1986). The majority of Bacillus species have been considered to be harmless, except for Bacillus anthracis.…”
mentioning
confidence: 99%